The power and discrimination of women as seen in jane austen’s Pride and prejudice - Gesmaloni Gesmaloni (Fakultas Sastra Universitas Ekasakti, 2017)
There is always discrimination against women in any field, as experienced by the main character Elizabeth Bennet in the novel Pride and Prejudice. Because women can not accept the inheritance from their fathers, therefore women are required to marry rich men to improve social class and economic life. Discrimination of women in the inheritance of wealth makes women have to struggle in finding rich men to marry. In the data analysis method the author performs a systematic procedure with a novel understanding, the main character of Elizabeth Bennet and also feminist theory, the technique used in this research is a structural technique by analyzing novels based on the elements that make up. The results of this study found that: 1) the discrimination of women in the inheritance of his father's estate, 2) the main character of Elizabeth Bennett describes the strength of women, because of his firm and wise in facing all problems in his life, 3) the women's struggle was carried out by Elizabeth Bennet in Find his true love and marry on the basis of love until it ends happily, but so many obstacles he faces both from the outside and from himself.